Patten recognition and informaiton forensics : ICPR 2018 International Workshops, CVAUI, IWCF, and MIPPSNA, Beijing, China, August 20-24, 2018, revised and selected papers /: ICPR 2018 International Workshops, CVAUI, IWCF, and MIPPSNA, Beijing, China, August 20-24, 2018, revised and selected papers. (2019) - Unknown
No abstract available